THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Rahmi Hermawati; Eni Puji Astuti; Rima Handayani (International Journal Management and Economic, 2024)
This research aims to investigate the impact of motivation and work environment on employee performance at the Depok City Public Works and Spatial Planning Department, both partially and jointly. The research method is quantitative with an associative approach, with questionnaires collecting data. The population studied was 106 people, and the sample was selected using a saturated sampling technique of 106 people. Data analysis includes validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficient tests, and determination. The research results show that motivation partially significantly affects employee performance. Likewise, the work environment also partially significantly affects employee performance. Simultaneously, motivation and work environment also significantly affect employee performance. The results of the determination test show that motivation and work environment contribute 61.5% to employee performance, while other factors influence the remaining 38.5%.